Kajian Pengaruh Kompleksitas Proyek terhadap Contingency Budget dan Kinerja Proyek - , OKTIYANTO ADE S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The uniqueness of the project led to the difficulty for managing project, as well as managing the total cost of the project. Contingency budget is one component of the project total cost which is not easy to be determined. Capability to manage and determine contingency budget are very necessary in the next competitive bidding era. These capabilities can help project practitioners win every project tender. In this study, project complexity approach is used to predict the project contingency budget, where complexity is a broader concept than the concept of risk, which has been used as a predictor of contingency budget. Development of instrument that can measure the level of project complexity has been successfully carried out by adopting the earlier studies. This study used 90 respondents, i.e.: practitioners who represented the existing projects in Indonesia. The sampling technique used was purposive sampling. Later, validity test, reliability test and exploratory factor analysis were used to the instrument for classifying and determining number of valid variable(s). The instrument that had been analyzed then was used to measure the relationship of project complexity, contingency budget and project performance in Indonesian. Analysis was also performed to describe the condition of the complexity level, contingency budget allocation, and also successful performance of projects budget in Indonesia The result of this study is an instrument that had been tested using exploratory factor analysis. The result of the study shows that the average level of complexity of the project in Indonesia is at level 3 of 4, where 4 is a condition with the highest level of complexity. In addition, it seems that the project contingency budget allocation in Indonesia is at level 2 of 4, i.e.: 1 % to 21 % of the total value of the overall project. Based on linear regression and multiple linear regression analysis can be explained that there is no significant relationship between project complexity and project contingency budgets in Indonesia. This raises the suspicion that the complexity project concept has not been used in determining the project contingency budget allocation on some projects in Indonesia or a more comprehensive study of the complexity concept in Indonesia is needed.